Clinical Profile of Adverse Cutaneous Drug Reactions in Patients with Human Immunodeficiency Virus - Puteri Nabilah Maharani; Oki Suwarsa; Susantina Prodjosoewojo (Faculty of Medicine Universitas Padjadjaran, 2020)
Background: Adverse cutaneous drug reactions (ACDRs) are common problems in patients during the treatment of various diseases. The clinical feature varies from mild manifestation such as morbilliform, urticaria, and contact dermatitis, to severe manifestation such as Stevens - Johnson syndrome (SJS) and Toxic Epidermal Necrolysis (TEN). Patients infected with the human immunodeficiency virus (HIV) have an increased risk of developing ACDRs due to immune system disruption. This study aimed to describe the clinical features of ACDRs in HIV patients and the drugs that cause ACDRs.Method: This study was a retrospective study using secondary data from medical records of HIV patients with ACDRs who visited Teratai Clinic of Dr. Hasan Sadikin General Hospital Bandung from 2014 to 2018. Total sampling was applied and results were presented in percentage.Results: There were 94 HIV patients with ACDRs out of 557 HIV patients. Adverse cutaneous drug reactions are commonly found in males aged 20-39 years old. The clinical features found were morbilliform (85.6%), SJS (8.9%), urticaria (4.4%), and erythroderma (1.1%). The most common drugs causing ACDRs were Cotrimoxazole (30%), Efavirenz (28.9%), and Nevirapine (16.7%).Conclusion: The prevalence of ACDRs in HIV patients in this study is 16.9%. The most common clinical features are morbilli form and SJS with Cotrimoxazole, Efavirenz, and Nevirapine causing most of the ACDRs.